(untitled) (Konferensiyalar | Conferences, 2024)
This thesis explores how ethnic and cultural factors influence modern teacher education, using a comparative approach to analyze experiences at regional, national, and international levels. It contends that the growing diversity of students requires a shift towards teaching methods that are culturally responsive and promote inclusivity within teacher training programs. The research delves into several key areas, including addressing the lack of diversity among teachers, managing linguistic differences, and nurturing intercultural skills and global citizenship among prospective educators. By examining various models and successful approaches, the thesis suggests recommendations for creating a more fair and inclusive education system that adequately prepares teachers to meet the needs of all students in today’s world.